ISLAMIC YOUTH RELATIONS AND SOCIAL MEDIA IN BUILDING SOCIAL SOLIDARITY - Tsulis Amiruddin Zahri; Putri Handayani Lubis; Syaifuddin Ahrom (Yayasan Literasi Kita Indonesia, 2021)
This study describes the construction of social solidarity built by Muslim youth in Indonesia through social media. Researchers in compiling this study used thematic analysis and literature related to the research theme. Islam as a religion has universal value in building social solidarity through the teaching that believers are like one body, which are interrelated. The parable that was conveyed by the Prophet Muhammad SAW which was narrated by Muslims became social capital that Islam could become an agent of unity in the country of Indonesia. Seeing the phenomenon of the flow of information that is so easy on social media, of course, it is hoped that the message of unity will be able to move Islamic youth who arenow dominating cyberspace to build social solidarity towards National Resilience.